2015
DOI: 10.1002/pssa.201532509
|View full text |Cite
|
Sign up to set email alerts
|

Mott–Schottky analysis of flower‐like ZnO microstructures with constant phase element behavior

Abstract: ZnO was prepared using room temperature bipolar electrochemical process in deionized water. Electron microscopy, powder X‐ray diffraction, and micro‐Raman spectroscopy showed crystallization of the material into the wurtzite hexagonal structure of ZnO, self‐organized in micro‐sized flower‐like shapes that are formed out of individual nanorods preferentially grown along the <0thinmathspace0thinmathspace0thinmathspace1> direction. The intrinsic electronic properties were evaluated by potentiodynamic electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The Mott-Schottky plots exhibited frequency dispersion indicating surface states, a trend observed in most nanostructured films. [30][31][32] The donor concentration of the films (measured from the slope of the 1/C 2 vs E plots) ranged from 3.6 × 10 17 cm −3 (at 18.2 kHz) to 1.57 × 10 19 cm −3 (at 1.1 kHz), based on a relative dielectric constant of 19.5. [33] The flat-band potential (E fb ) obtained from the x-intercept of the 1/C 2 versus E plots, showed narrow ranges from 0.17 V versus RHE (at 1.1 kHz) to 0.20 V versus RHE at (18.2 kHz).…”
Section: Hydrogen Productionmentioning
confidence: 99%
“…The Mott-Schottky plots exhibited frequency dispersion indicating surface states, a trend observed in most nanostructured films. [30][31][32] The donor concentration of the films (measured from the slope of the 1/C 2 vs E plots) ranged from 3.6 × 10 17 cm −3 (at 18.2 kHz) to 1.57 × 10 19 cm −3 (at 1.1 kHz), based on a relative dielectric constant of 19.5. [33] The flat-band potential (E fb ) obtained from the x-intercept of the 1/C 2 versus E plots, showed narrow ranges from 0.17 V versus RHE (at 1.1 kHz) to 0.20 V versus RHE at (18.2 kHz).…”
Section: Hydrogen Productionmentioning
confidence: 99%
“…Obviously, the smallest Tafel slope and η of rGAA-2 reflect the high-efficient catalytic hydrogen production, [79][80][81] which is matched with the HER results. 82,83 Based on aforementioned research, the VLD catalytic mechanism of rGAA-α catalyst was confirmed to be the model as Figure 9. Generally, in M-S plots, the positive and negative slope of the linear region represent the electron donor characteristic and electron acceptor characteristic.…”
Section: Catalytic Mechanismmentioning
confidence: 75%
“…However, both the electron donor effect and electron receptor effect can be found in rGAA-2 composite for the obvious positive and negative slope in its M-S plots ( Figure 8E), suggesting that the effective electron transfer system (heterointerface) was constructed between AgBr and rGO, so that the electrons can easily transfer to the AgBr catalyst from rGO structure. 82,83 Based on aforementioned research, the VLD catalytic mechanism of rGAA-α catalyst was confirmed to be the model as Figure 9. The VB potential of rGO is confirmed as 2.13 eV by XPS VBs analysis, and it is well known that the HOMO of rGO is very close to its LUMO, 84,85 so that its π→π* transition can easily be induced by visible-light.…”
Section: Catalytic Mechanismmentioning
confidence: 75%
“…The dielectric and insulating properties at the electrode/electrolyte interface can be indicated by R ct and Q . On the other hand, the heterogeneity of the electrode/solution interface is related to Q . The change in redox on the surface of the electrode can be manifested by a change in R ct .…”
Section: Resultsmentioning
confidence: 99%